The Role of Kyai and Asatidz in Developing Islamic Teachings Among Students at the Ianatut Tholibin Mojokerto Islamic College - Auliya, Najwa Zuhrotul; Ilmiyah, Nihayatul; Saniya, Siti Nur (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3775, 2025)
This qualitative phenomenological study analyzes the strategic roles of Kyai and Asatidz in creating Islamic values at the I'anatut Tholibin Islamic Boarding School in Mojokerto. The study aims to analyze the process of forming Islamic values through in-depth interviews, participatory observation, and document studies. The results show that these boarding schools remain relevant in the modern era due to their integrative educational approach. A strong emphasis on moral education through direct role modeling is combined with a scientific foundation based on the Qur'an, Hadith, and the classical Shafi'i fiqh texts. Traditional learning methods such as sorogan and bandongan, a comprehensive evaluation system that considers both cognitive and affective aspects, and an educational disciplinary approach support the educational process. Kyai and Asatidz perform various tasks, including teaching, providing spiritual guidance, and exemplifying a life of practice. Although it has advantages in maintaining academic authenticity and character building, this pesantren faces challenges in broadening knowledge across different schools of thought, preparing for the digital era, and confronting the threat of social isolation. This study shows that the traditional pesantren education model is still relevant for strategic changes to address current challenges while maintaining a true Islamic identity.